ЕNGINEERING EDUCATION, BUSINESS AND MANAGEMENT OF INTELLECTUAL PROPERTY - Sergey R. Borisov; Boris N. Korobets (Высшее образование в России)
The article describes the activities of the complex Innovation Ecosystem formed at Bauman MSTU, considers its separate structural elements, their task and functional duties. The complex Innovation Ecosystem combining modern educational technologies and real business processes has to become the center uniting science and innovatics, training in business and management of high technologies at University.